Circulating miR-122 Is a Predictor for Virological Response in CHB Patients With High Viral Load Treated With Nucleos(t)ide Analogs - Wu, Yin; Gao, Chang; Cai, Shaohang; Xia, Muye; Liao, Guichan; Zhang, Xiaoyong; Peng, Jie (Frontiers in Genetics, 2019)
Chronic hepatitis B (CHB) infection remains worldwide health problem. Antiviral treatment options for CHB patients include nucleos(t)ide analogues (NAs) and interferon. Most of the current biomarkers for predicting treatment response are virus-dependent. MicroRNA-122 is the most abundant liver-specific miRNA and has been identified involved in multiple liver physiology and pathology including hepatotropic virus infection. To identify the role of miR-122 in NA therapy, 80 CHB patients with high viral load were enrolled and serum miR-122 expression at baseline, week 12 and week 24 were measured. Serum miR-122 levels were significantly lower in patients who developed virological response (VR), compared with non-VR group. Expression of miR-122 at week 12 and week 24 were determined to be independent prognostic indicators for a VR with satisfactory AUROC values at 0.812 and 0.800 respectively. During NA therapy, serum miR-122 expression deceased steadily and an earlier reduction was observed in VR group, indicating early reduction of miR-122 expression might increase the possibility of developing virological response. In conclusion, we identified the dynamic change of serum miR-122 expression and miR-122 expression at week 12 and week 24 as independent predictors for virological response in CHB patients with high viral load treated with NAs.